Hubungan Empathy dengan Loneliness pada Anak Panti Asuhan Evangeline Booth dan Wiliam Both Medan - Yunike Cheria; Gloria Tarafang; Setiyo Wibowo; Calvian Tanur; Aleksander Agung Wijaya; Diny Atrizka (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the relationship between empathy with loneliness of children at the Putri Evangeline Booth Orphanage and Putra Wiliam Booth Orphanage. This research was conducted at Putri Evangeline Booth Orphanage located on Jl. Samanhudi No. 27, Hamdan, Medan and the Putra Wiliam Booth Orphanage located on Jl. K. L. Yos Sudarso No. 10, Medan. This study uses primary data for hypothesis testing. While the data collection method used is a questionnaire that was distributed to the study sample. The sample used in this study were 101 respondents. Data analysis technique used in this research is to use Pearson Product Moment correlation analysis method which is done with the help of SPSS 25 for Windows software. The results of data analysis show that the correlation value of product moment is -0.868. This means that there is a negative relationship between empathy and loneliness. The influence of empathy variable on loneliness is 75.3 percent, the remaining 24.7 percent is influenced by other factors not examined. From this study, we can also know that empathy held by children at Putri Evangeline Orphanage and Putra Wiliam Booth Orphanage are included in the high category. Loneliness felt by children is included in the low category. And empathy was proven to have a negative and significant relationship to loneliness in children raised at Putri Evangeline Orphanage and Putra Wiliam Booth Orphanage.